Structures and data preserving homomorphic signatures. (15th January 2018) - Emmanuel, Naina; Khan, Abid; Alam, Masoom; Khan, Tanveer; Khan, Muhammad Khurram
Abstract: Homomorphic Signatures (HS) are used to provide credentials of the results that are computed by a given function on some dataset by some untrusted party like a cloud. The input data is stored on a cloud with its signatures before hand. Since, recent advances have raised success and popularity of cloud computing and data outsourcing. Thus, homomorphic signatures and data verification along with the privacy of original data have become a critical concern. Motivated by the vast potential of homomorphic signature's applications, we are providing the comprehensive survey on existing homomorphic signature schemes covering signatures from different aspects: Linear HS, Key-Homomorphism, Short HS, Lattice-based HS and HS for Polynomials. We are providing a detailed categorization of the schemes and their taxonomy. Security and performance analysis has been performed on these HS schemes. This paper is providing a timeline of the HS from their inception and explores usage and limitations inherent to the homomorphic signature schemes in untrusted environment.